Peningkatan Kemampuan Kognitif pada Anak Disleksia Melalui Treatment Kemampuan Mengeja, Membaca, dan Menulis - Martha, Salsabila Auralia; Raharjo, Trubus (Universitas Mathla'ul Anwar Banten, 2024)
Generally, elementary school age children experience a significant increase in cognitive development. Obstacles in cognitive development, one of which is an obstacle to the brain, which is related to the central nervous system can affect children's learning ability. Learning disorders experienced by children can be called dyslexia. The purpose of this study is to determine the effectiveness of spelling, reading, and writing skills treatment to improve cognitive abilities in dyslexic children. This study uses an experimental research method with a pre-experimental design. The sampling technique used in this study is the purposive sampling technique. The subjects of this study were 10 elementary school children who had been diagnosed with dyslexia by psychologists and were undergoing therapy at the Kudus Dyslexia School. The researcher used the Wilcoxon Signed Rank Test as an application in analyzing the data. Based on the results of the study, it was found: 1) a decrease in the score of the number of errors before and after the treatment. 2) There is an improvement in cognitive ability in dyslexic children after being given treatment for spelling, reading, and writing skills.